Sistem Informasi Pengukuran Kadar Hemoglobin Non-Invasif Berbasis Android Menggunakan Algoritma Extreme Gradient Boosting - Syarifuddin, Sri Dewi Sartika; Khurniawan, Amri; Munadi, Rendy; Sussi, Sussi (Computer Engineering Departement, Universitas Komputer Indonesia, 2023)
Measurement of hemoglobin levels nationally was carried out invasively using the sahli method of 27.9%. Measurement of invasive hemoglobin levels takes a long time due to the chemical analysis of patient blood samples in the blood laboratory. In general, blood sampling is done using a syringe, which can cause pain and increase the risk of spreading other diseases through needle-stick wounds. Measurement of hemoglobin levels can be done using multiwavelength oximetry technique. Therefore, in this study, a non-invasive real-time measurement system for hemoglobin levels based on the internet of things was created using the multiwavelength oximetry technique with the Extreme Gradient Boosting algorithm which is integrated with Real-time Database and an android-based information system capable of mapping users using QR Code. The test results using the RMSE parameter obtained a value of 0.801085 which indicates a high category level and an accuracy of 94.91%. The information system can display real-time measurement of hemoglobin levels with a delay of 317 ms and a throughput of 3138 bps. The results of testing the oxygen saturation functionality are 0.654% with the difference in the measurement value of the highest oxygen saturation level being 1.33% and the smallest being 0.08%.